LIFE CYCLE COST ANALYSIS OF HOUSEHOLD DESIGN WIRASAKTI HOSPITAL, KUPANG CITY - Gregorius Paus Usboko; Merzy Mooy; Sri Santi M L F Seran (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
Kupang City has development potential because it is still classified as a developing city. In general, the Wirasakti Hospital building construction project in the city of Kupang has implemented the project management concept well, but there are still a number of things that need to be considered in order to use costs efficiently and effectively. The building elements that are reviewed and analyzed are the stair elements in the building project by considering several aspects, namely the cost aspect, the comfort aspect and the aesthetic aspect. This research presents an algorithm for choosing the best alternative field among various stair design structures (staircase types) using Life Cycle Cost. Economic efficiency (removing and replacing secondary functions), landscaping, construction capabilities, function of building elements (replacing systems) are considered in the planning of stair elements. Replacing the system, eliminating and replacing secondary functions are evaluated for each plan for each alternative plan with optimal design taking into account the life cycle cost (LCC). The results of the Life Cycle Cost analysis are obtained as alternative stairs which are selected using stair beam materials with calcide/calcistair, stair plates with hollow iron and glass railings & stainless steel pipes.